Wound healing effect of nutmeg (Myristica fragrans) cream on second-degree burn in animal model - Angilia, Ciecielia; Sary, Nirwana L.; Indah, Rosaria; Suryawati, Suryawati; Farsa, Bianda S.; Zeir, Haya A.; Fajri, Fauzan; Husna, Fauzul (Narra Sains Indonesia, 2024)
Second-degree burn, the most common among burn degrees, underscores the importance of timely and proper treatment in influencing prognosis. Nutmeg (Myristica fragrans), renowned for its potent antibacterial and antifungal properties, also serves as an effective antiseptic for open wounds. The aim of this study was to identify the phytochemical constituents of nutmeg essential oil and analyze the wound healing effect of nutmeg cream on second-degree burns in an animal model. An experimental study with a completed randomized design was conducted on Rattus norvegicus strain Wistar rats with second-degree burn. This study had four groups and each group consisting of four rats: B (burn-treated base cream), B+N (burn-treated 3% nutmeg cream), B+SSD (burn-treated silver sulfadiazine (BSS)), and B+N+SSD (burn-treated 3% nutmeg cream and SSD in a 1:1 ratio). The phytochemical analysis of nutmeg essential oil was conducted by gas chromatography and mass spectroscopy (GC-MS). The burn diameter and burn wound healing percentage were measured from day 0 to 18. One-way ANOVA followed by post hoc analysis using the least significant difference (LSD) was employed to analysis the effect. The phytochemical analysis of nutmeg essential oil found that myristicin, terpinene-4-ol, terpinene, safrole and terpinolene were the most abundant putative compounds in nutmeg essential oil. On day 0, the average burn wound diameters were 1.4 cm in all groups and increases were observed in all groups in day 3. The wound diameter decreased until day 18 with the smallest burn wound diameter was found in the B+N group (0.86±0.37 cm), followed by B+SSD (0.93±0.29 cm). The B+SSD group exhibited the highest percentage of burn wound healing (56.80±14.05%), which was significantly different from the base cream (p<0.05). The percentage of burn wound healing in rats given 3% nutmeg cream was 41.88±13.81% suggesting that nutmeg cream could promote burn wound healing in rats induced by second-degree burns.